Ultrasensitive detection of programmed death-ligand 1 (PD-L1) in whole blood using dispersible electrodes. Issue 20 (15th February 2021) - Moazzam, Parisa; Myekhlai, Munkhshur; Alinezhad, Ali; Alshawawreh, Fida'a A.; Bakthavathsalam, Padmavathy; Gonçales, Vinicius R; Tilley, Richard D.; Gooding, J. Justin
Abstract : A rapid, selective, and highly sensitive electrochemical-based sensing platform that uses the Au@MNPs as dispersible electrodes for quantifying programmed-death ligand 1 (PD-L1 ) levels directly in undiluted whole blood. Abstract : The direct quantification of programmed death-ligand 1 (PD-L1 ) as a biomarker for cancer diagnosis, prognosis and treatment efficacy is an unmet clinical need. Herein, we demonstrate the first report of rapid, ultrasensitive and selective electrochemical detection of PD-L1 directly in undiluted whole blood using modified gold-coated magnetic nanoparticles as "dispersible electrodes" with an ultralow detection limit of 15 attomolar and a response time of only 15 minutes.